Factors Affecting Herbicide Use in Fruits and Vegetables - C. E. Rouse; Peter J. Dittmar (EDIS)
Proper herbicide application is critical for fruit and vegetable growers to effectively manage weeds. Improper herbicide application may lead to herbicide loss from the targeted area, increased crop injury, and reduced weed control. Growers need to take into account a number of factors before and during application in any crop to ensure the herbicide is effective. Herbicide efficacy is greatly affected by timing and environmental conditions. Although complete weed control is not always possible, even slight reductions in weed populations can greatly enhance productivity in fruit and vegetable crops. This 4-page fact sheet reviews techniques and processes to help growers properly apply herbicides. Understanding the processes and applying the following techniques will help to increase the overall efficacy of herbicides in fruit and vegetable production. Written by C. E. Rouse and P. J. Dittmar, and published by the UF Department of Horticultural Sciences, May 2013.